Growth Mindset of Quality Management in an Islamic School - Dr. Denny Kodrat (Perhimpunan Intelektual Muslim Indonesia, 2020)
The work aims at clarifying how the growth mindset plays a vital role in quality management at the Islamic school. As an active response towards industrial revolution 4.0, an Islamic school is faced with complex external challenges, from the issue of radicalism, anti-multiculturalism to tight competitiveness with the public (general) school. An Islamic school tends to feel satisfied with the output that school graduates are Al-Quran memorizers, while the school seems to ignore the input and process. At the same time, the government has stipulated the regulation dealing with national education standards being followed by educational stakeholders. Eight national educational standards become a reference in Islamic school quality management. The school is urged to provide human resources to meet the requirements. Library research was intensively carried out. Growth mindset becomes an essential basis in Islamic schools in developing quality concern as a total quality management philosophy requires continuous improvement tradition. Without a growth mindset in quality management at Islamic schools, quality improvement and school competitiveness are difficult to reach. This manuscript employed some theoretical references, such as mindset and quality.